Suitable reference genes for RT-qPCR analysis in Dichelops melacanthus (Hemiptera: Pentatomidae) - Pinheiro, Daniele Heloísa (2020)
The relative quantification of gene expression is mainly realized through reverse transcription-quantitative PCR (RT-qPCR). However, the accuracy of this technique is deeply influenced by the expression stability of the reference genes used for data normalization. Therefore, the selection of suitable reference genes for a given experimental condition is a prerequisite in gene expression studies. Dichelops melacanthus (Hemiptera: Pentatomidae) is an important phloem sap-sucking insect pest of soybean, wheat, and maize in Brazil. Most of the genetic and molecular biology studies require gene expression analysis. Nevertheless, there are no reports about reference genes for RT-qPCR data normalization in D. melacanthus. In this study, we evaluated the expression stability of nine candidate reference genes (nadh, sdhb, gapdh, fau, ef1a, rpl9, ube4a, gus and rps23) in different developmental stages, body parts, sex, starvation-induced stress and dsRNA exposure by RefFinder software that integrates the statistical algorithms geNorm, NormFinder, BestKeeper, and ΔCt method. Our results showed that ef1a and nadh are the most stable reference genes for developmental stages, fau and rps23 for sex, ube4a and rps23 for body parts, rpl9 and fau for starvation stress, and nadh and sdhb for dsRNA exposure treatment. The reference genes selected in this work will be useful for further RT-qPCR analyses on D. melacanthus, facilitating future gene expression studies that can provide a better understanding of the developmental, physiological, and molecular processes of this important insect pest. Moreover, the knowledge gained from these studies can be helpful to design effective and sustainable pest management strategies.